Computer graphics in medicine - Sayfullayev Ramziddin Fazliddin o’g’li; Musayev Obid Saylidinovich; Raxmonov Kamol Samadovich (Genius Journals, 2023)
In the article, the main difficulties that surgeons face when performing laparoscopy are Limited camera field of view , the fact that the monitor reflects a mirror image of the real movements of surgical instruments, tactile effects (force feedback) of surgical seals are significantly reduced due to the distance from the end of the instruments to the hands of the surgeon, The fact that surgical instruments most of all rotate around a fixed point, which makes movement difficult.
Keywords: graphics; laparoscopy; Filtering and segmentation; Algorithms and methods